Nanogels as potential nanomedicine carrier for treatment of cancer: A mini review of the state of the art - Govind Soni; Khushwant S. Yadav (Elsevier, 2016)
Nanogels are being explored as drug delivery agents for targeting cancer due to their easy tailoring properties and ability to efficiently encapsulate therapeutics of diverse nature through simple mechanisms. Nanogels are proficiently internalized by the target cells, avoid accumulating in nontarget tissues thereby lower the therapeutic dosage and minimize harmful side effects. However, there is an urgent need for relevant clinical data from nanogels so as to allow translation of the nanogel concept into a viable therapeutic application for the treatment of cancer. This review highlights some of the recent progress in nanogels as a carrier in the field of nanomedicine for the treatment of cancer. The present review critically analyzes the use of extracellular pH targeting for nanogels, siRNA delivery, PEGylated nanogels, multi-responsive nanogels and intracellular delivery of nanogels for improved therapy of cancer.